On the dynamics of two-dimensional dissipative discontinuous maps - Perre, Rodrigo M. [UNESP]; Carneiro, Bárbara P. [UNESP]; Méndez-Bermúdez, J. A.; Leonel, Edson D. [UNESP]; de Oliveira, Juliano A. [UNESP] (Elsevier, 2020)
Some dynamical properties for a dissipative two-dimensional discontinuous standard mapping are considered. The mapping, in action-angle variables, is parameterized by two control parameters; namely, k ≥ 0 controlling the intensity of the nonlinearity and γ ∈ [0, 1] representing the dissipation. The case of γ=0 recovers the non-dissipative model while any γ ≠ 0 yields to the breaking of area preservation; hence leading to the existence of attractors, including chaotic ones. We show that when starting from a large initial action, the dynamics converges to chaotic attractors through an exponential decay in time, while the speed of the decay depends on the dissipation intensity. We also investigate the positive Lyapunov exponents and describe their behavior as a function of the control parameters.
Keywords: Chaotic attractors; Dissipative discontinuous standard mapping; Lyapunov exponents